The Effects Of Negotiator Preferences, Situational Power, And Negotiator Personality On Outcomes Of Business Negotiations - Greenhalgh, Leonard; Neslin, Scott A.; Gilkey, Roderick W. (Academy of Management Journal, 1985)
A laboratory experiment was used to investigate the joint effects of preferences, personality, and situational power on the outcomes of business negotiations. Results show that preferences vary across negotiators and directly determine outcomes; the effects of personality and power are significant but are mediated by preferences.